PERUBAHAN KEBIJAKAN LUAR NEGERI INDONESIA TERHADAP ISU NUKLIR IRAN DI DEWAN KEAMANAN PBB TAHUN 2007-2008 - Asep Setiawan; Yanyan Mochamad Yani (Universitas Komputer Indonesia, 2019)
This study is aimed to analyze Indonesia’s foreign policy changes toward Iranian nuclear issue in The United Nations Security Council (UNSC) from 2007 to 2008. The Iranian nuclear issue became international focus when UNSC in 2006 decided the future of Iranian nuclear program. Nuclear proliferation’s threat was debated in UNSC due to a new nuclear program launched by Iranian President Mahmoud Ahmadinejad to build nuclear arsenal as soon as possible. As a non-permanent member of UNSC, Indonesia should participate in any decision within two years whether to support, abstain or to reject any resolutions decided. The research used qualitative method with a case study type. Data was collected based on qualitative method through literature study and interviews in order to gain understanding why the changes occurred in Indonesia’s foreign policy with domestic and international factors as consideration. The research concluded that Indonesia’s foreign police changes was on international pressure to support new sanction on Iranian nuclear program in 2007. Indonesia’s policy was criticized in domestic. After domestic pressure, Indonesia finally took abstain policy in a new resolution on Iran nuclear in UNSC on March 2008. In other words the Indonesian foreign policy changes can be classified in adjustment changes to appease domestic pressure and in the same time to avoid confrontation with major powers interests.